Futebol, negócio e globalização: clubes brasileiros na nova era do multi-club ownership - Santos, Irlan Simões; Ferreira, Jonathan [UNESP]; Pisani, João Ricardo (Universidade de São Paulo, 2022)
Soccer has acquired new forms of organization in a period marked by the technical-scientific-informational milieu, in which companies become globalized. The appropriation of local soccer clubs by global companies and businessmen is one of such forms. Often, these businesses own more than one club, a process known as MCO (multi-club ownership). US-based private capital has considerably increased its interest in soccer worldwide and has channeled large investment into the sport. In Brazil, the sales of 90% ofSociedade Anônima do Futebol (SAF) Botafogo and of 70% of SAF Vasco for American investors in 2022 are major examples of such phenomenon. This study analyzes the interaction within those soccer clubs’ networks since the development of MCO, with a closer look at the new wave of US investments in soccer clubs in Brazil in the past few years. This article attempts to answer the question: Does this investment trend reinforce a subordinated insertion/introduction of clubs in an operational organization in networks? The present trend of US investment in soccer clubs in Brazil was perceived to deepen the phenomenon of MCO, enabling the subordination of local clubs to a centralized structure, especially since the implementation of SAFs.

O futebol adquiriu novas formas de organização em um período marcado pelo meio técnico-científico-informacional, em que empresas se tornam globais. Dentre essas maneiras, está a apropriação de clubes de futebol locais por empresários e corporações globais, que recorrentemente se tornam proprietários de mais de um clube. Para designar a existência de diversas agremiações controladas pelo mesmo proprietário, utiliza-se a sigla MCO (multi-club ownership). O capital privado sediado nos Estados Unidos tem aumentado consideravelmente seuinteresse no futebol e canalizado largos investimentos no esporte. No Brasil, a venda de 90% da Sociedade Anônima do Futebol (SAF) de Botafogo de Futebol e Regatas e 70% da SAF Club de Regatas Vasco da Gama para companhias norte-americanas em 2022 são os principais exemplos desse fenômeno. Este estudo analisa a interação em redes de clubes de futebol a partir do surgimento de MCO, com ênfase na nova onda de investimentos estadunidenses em clubes de futebol no Brasil. O artigo busca responder a seguinte questão: esta onda de investimento reforça a introdução subordinada dos clubes numa organização operacional em redes? Observou-se que a onda atual de investimentos dos EUA em clubes de futebol no Brasil ampliou o fenômeno de MCO, permitindo a subordinação de clubes locais a uma estrutura centralizada, especialmente a partir da implementação das SAFs.
Soccer, business and globalization: brazilian clubs in the new era of multi-club ownership
Keywords: Sociedade Anônima do Futebol; SAF; Clube-empresa; Redes; Brasil; Futebol; Limited soccer companies; Networks; Brazil; Soccer